KONFLIK BATIN TOKOH AKU DALAM CERPEN ”IZU NO ODORIKO” KARYA KAWABATA YASUNARI - Zumanto, Bahri (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Diponegoro, 2013)
Zumanto, Bahri. “Konflik Batin Tokoh Aku Dalam Cerpen ‘Izu No Odoriko’ Karya Kawabata Yasunari”. Thesis. Japanese Literature Department. Faculty of Humanities Diponegoro University. Pembimbing I.Drs. Redyanto Noor, M.Hum. Pembimbing II. Zaki Ainul Fadli, S.S, M.Hum The purpose of this study is analyze the psychology of the main character in the short story izu no odoriko. The data used in this study is the short story izu no odoriko, published by Kawabata Yasunari in 1926. Theory used in this research is the theory of structuralism and psychoanalysis by Sigmund Freud. the main character of izu no odoriko is Kaoru, and subordinate character are Eikichi, Chiyoko, Yuriko, and a woman aged forty years. The flow in this short story is a single path in the form of grooves are not straight. events recounted are not sequentially, sometimes flashbacks. Background used in the short story izu no odoriko is Amagi, Yugano, and Shimoda Themes in this short story is sadness. There are so many sad story along this short story. Mandate in the short story is provides another viewpoint of Izu dancer’s life. Another message about perseverance in the face of the trials of life but ends happily. Based on the analysis of psycho-analysis, can be disclosed that the inner conflict that occurs in the main character triggered a sense of love with izu dancer named Kaoru. But in the end the main character back to Tokyo with a heart of peace for having shared with the izu dancers.